Sociolinguistic Aspects in Javanese Monologue Speech: A Case Study of ‘Ngangkataken Ulem at Dusun Kretek, Ungaran’ - Aini, Veny Nur (CV. Publikasi Indonesia, 2024)
Every situated text is modified by the social forces in its particular context. The present study examined the context of a Javanese monologue text in a case study of ‘Ngankataken Ulem’ speech. This study is interested in analysis the generic components of the speech to determine the communicative purpose and to know the linguistic repertoire in use of the speech. Data were collected through observation, unstructured interviews, and document analysis.. As the result, it could be concluded that ‘Ngangkataken Ulem’ speech used krama inggil that was the highest level of politeness in Javanese language as its linguistic choice. The aim was to respect and to persuade the addressee, hopefully they were able to fulfil the invitation.